Academic Supervision and GROW Coaching Model Implementation in Junior Secondary Science Teaching - Vikto Agus Wibowo; Rosmawati Rosmawati; Nyoto Suseno; Agus Sujarwanta (Penerbit Goodwood, 2026)
Purpose: This study evaluates academic supervision combined with the Goal Reality Options Will (GROW) coaching model for a junior secondary science teacher, describing how supervision and coaching jointly support instructional quality and identify barriers to classroom conducivity.Methodology: A descriptive case study was conducted at SMPN 4 Mesuji, Lampung, involving one science teacher and one grade VIII class during a Problem Based Learning (PBL) lesson on the human digestive system, using a lesson-plan checklist, an observation instrument, a coaching-practice rubric, a structured interview, and the GROW coaching protocol, analyzed descriptively through instrument scoring formulas.Results: The learning-process observation instrument recorded 42 fully implemented indicators, 3 partially implemented, and 1 not implemented, producing a raw score of 89 and a final score of 94.7, categorized as very good. The coaching-practice rubric produced 19 of 20 possible points, equivalent to a final score of 95, also categorized as very good. Interview and GROW coaching data revealed classroom conducivity and unattractive instructional media as the dominant obstacles, with Canva-based media redesign proposed as corrective action.Conclusions: Supervision paired with GROW coaching effectively surfaces actionable instructional problems even when overall teaching performance is already rated very good. Limitations: Findings rest on a single teacher and single lesson observation, limiting generalization.Contributions: The study offers a replicable supervisioncoaching protocol and scoring framework for science teacher development in similarly resourced schools.